2006
DOI: 10.1124/jpet.106.108944
|View full text |Cite
|
Sign up to set email alerts
|

The Serotonin 5-Hydroxytryptaphan1A Receptor Agonist, (+)8-Hydroxy-2-(di-n-propylamino)-tetralin, Stimulates Sympathetic-Dependent Increases in Venous Tone during Hypovolemic Shock

Abstract: Adjuvant treatment of hypovolemic shock with vasoconstrictors is controversial due to their propensity to raise arterial resistance and exacerbate ischemia. A more advantageous therapeutic approach would use agents that also promote venoconstriction to augment perfusion pressure through increased venous return. Recent studies indicate that 5-hydroxytryptophan (5-HT) 1A receptor agonists increase blood pressure by stimulating sympathetic drive when administered after acute hypotensive hemorrhage. Given that ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
6
9
0
Order By: Relevance
“…Here, we demonstrated that a single bolus dose of 8-OH-DPAT increased CO throughout the 15-min postinjection recording period. In our prior study, 8-OH-DPAT increased arterial and mean circulatory filling pressure for the duration of a 35-min postinjection recording period (Tiniakov and Scrogin, 2006). Hematocrit and plasma protein levels were not affected by drug treatment in either the previous or present studies, indicating that increases in mean circulatory filling pressure and CO were most likely the result of altered venous tone and not differences in capillary refill.…”
supporting
confidence: 44%
See 4 more Smart Citations
“…Here, we demonstrated that a single bolus dose of 8-OH-DPAT increased CO throughout the 15-min postinjection recording period. In our prior study, 8-OH-DPAT increased arterial and mean circulatory filling pressure for the duration of a 35-min postinjection recording period (Tiniakov and Scrogin, 2006). Hematocrit and plasma protein levels were not affected by drug treatment in either the previous or present studies, indicating that increases in mean circulatory filling pressure and CO were most likely the result of altered venous tone and not differences in capillary refill.…”
supporting
confidence: 44%
“…Evidence from the present study supports these findings by demonstrating that 8-OH-DPAT promotes increased cardiac output. Previous studies indicated that venoconstriction is, in part, responsible for the rise in venous return (Tiniakov and Scrogin, 2006). However, additional studies suggested that 8-OH-DPAT may also increase cardiac output by virtue of its ability to stimulate epinephrine release (Bagdy et al, 1989a,b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations